1999
DOI: 10.1046/j.1440-1703.1999.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed leaf litter effects on decomposition rates and soil microarthropod communities in an oak–pine stand in Japan

Abstract: Rates of decomposition, and soil faunal abundance and diversity associated with single‐species and mixed‐species litters were studied in a litter bag experiment in an oak–pine forest. We used two canopy species of leaf litter, pine and oak, and one shrub species, Sasa, and compared decomposition rates, and soil microarthropod abundance and community structure of oribatid mites in the litter bags. Mass loss of single species decreased in the order: oak > pine > Sasa. While the total mass loss rates of mixed lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(120 citation statements)
references
References 21 publications
5
110
5
Order By: Relevance
“…In other words, increased abundance of decomposer fauna does not necessarily accelerate decomposition. These results are consistent with those of Kaneko and Salamanca [50], who found that faunal abundances in single-species litterbags were not correlated with mass loss. Our findings also agree with those of Standish [11], who found that rates of litter decomposition of an invasive herbaceous weed were not associated with an increase in the abundance of Collembola and Acari.…”
Section: Advances In Ecologysupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, increased abundance of decomposer fauna does not necessarily accelerate decomposition. These results are consistent with those of Kaneko and Salamanca [50], who found that faunal abundances in single-species litterbags were not correlated with mass loss. Our findings also agree with those of Standish [11], who found that rates of litter decomposition of an invasive herbaceous weed were not associated with an increase in the abundance of Collembola and Acari.…”
Section: Advances In Ecologysupporting
confidence: 92%
“…We propose a compensation produced by a lower quality but more heterogeneous litter in the native forest and a higher quality but almost homogeneous litter in the invaded forest. It has been demonstrated that litter produced from mixtures of several plant species decomposes faster than material taken from isolated species [50,55].…”
Section: Advances In Ecologymentioning
confidence: 99%
“…Decrease in the abundance of Oribatids can also be caused by ash treatment of sour, acidic soils (Liiri et al, 2002). In Japanese coniferous forests it has been shown that the abundance of Oribatids was greater in mixed litter (litter of several tree species) than in litters consisting of only one tree species (Kaneko and Salamanca, 1999). Kovác et al, (2001) explored positive correlation between the nutrient content of the soil and abundance, but it was contradicted by several other studies (e.g.…”
Section: Abundance Species Richness and Diversity -Summarymentioning
confidence: 97%
“…Littermixing studies have focused on detecting these non-additive effects, both in terms of nutrient content of litter (Blair and others 1990;Klemmedson 1992;Rustad 1994;Wardle and others 1997;Salamanca and others 1998;Kaneko and Salamanca 1999;Conn and Dighton 2000;Madritch and Cardinale 2007) and its release from the litter (Chapman and others 1988;Williams and Alexander 1991;Fyles and Fyles 1993;Briones and Ineson 1996;McTiernan and others 1997;Brandtberg and Lundkvist 2004). Non-additive dynamics have been observed by some (Chapman and others 1988;Blair and others 1990;McTiernan and others 1997;Wardle and others 1997;Salamanca and others 1998;Kaneko and Salamanca 1999;Madritch and Cardinale 2007) and not by others (Klemmedson 1992;Rustad 1994;Brandtberg and Lundkvist 2004), even with the observation of both non-additive and additive effects in the same experiment (Fyles and Fyles 1993;Gartner and Cardon 2006). Although non-additivity is often observed, there is little evidence in the literature for any effect of species richness per se on nutrient dynamics, so it is likely species composition (identity) that drives these effects (Hä ttenschwiler and others 2005).…”
Section: Introductionmentioning
confidence: 99%